Thoracic Myelopathy Caused by Ossification of the Yellow Ligament as a Distal Adjacent Segmental Disease after Posterior Cervical-Middle Thoracic Fusion Surgery - Toru Funayama; Kentaro Mataki; Tetsuya Abe; Hiroshi Noguchi; Kousei Miura; Hiroshi Kumagai; Katsuya Nagashima; Yosuke Shibao; Kosuke Sato; Masao Koda; Masashi Yamazaki (Case Reports in Orthopedics)
Although adjacent segmental disease after posterior thoracic fusion surgery is rare, thoracic myelopathy due to ossification of the yellow ligament in the lower thoracic spine could develop because of mechanical stress when the lower instrumented vertebra has been set to the middle thoracic spine during the initial surgery. We report an extremely rare case of distal adjacent segmental disease after posterior cervical-middle thoracic fusion surgery requiring reoperation after exhibiting thoracic myelopathy due to ossification of the yellow ligament in the lower thoracic spine. An obese 53-year-old man with diabetes had undergone C3-6 laminoplasty and C7-T8 posterior decompression plus fusion due to ossification of the posterior longitudinal ligament at C5-T5. Although the short-term clinical course after the initial surgery was good, symptoms of myelopathy reappeared because of the ossification of the yellow ligament that developed at T9-11 with local flexibility. Thus, reoperation with fusion extension surgery was needed 1 year and 6 months after the initial surgery. Altogether, we recommend careful monitoring of the postoperative clinical progression and, if necessary, reoperation at the earliest.